Optimisation and financial analysis of an organic Rankine cycle cooling system driven by facade integrated solar collectors. (1st January 2017) - Wu, Dan; Aye, Lu; Ngo, Tuan; Mendis, Priyan
Highlights: A novel solar cooling system was developed for office buildings. The system uses solar energy collected at the façade to cool the building. The net present value of the electricity saving was maximised for the optimisation. The unit cost of cooling of optimised system is $0.24 per kWhr of cooling effect. Abstract: The use of a solar cooling system has the potential to reduce the amount of energy required for cooling buildings. One of the most important methods of improving energy efficiency in buildings is by carefully designing building façades. A façade integrated evacuated tube collector (ETC)-organic Rankine cycle (ORC)-vapour compression cycle (VCC) was applied in this study. To optimise the design parameters of ORC, a steady-state semi-empirical model was developed in Engineering Equation Solver (EES). The optimum number of plates in each heat exchanger is obtained by maximising the net present value (NPV) of electricity savings. The financial performance of the optimised system was assessed through a unit cooling cost (UCC) analysis. It was found that the UCC of the optimised facade integrated ETC-ORC-VCC system is $0.24 per kWhr of cooling effect.